Blood filtering system for COVID-19 management: novel modality of the cytokine storm therapeutics - Chavda, Vivek P.; Raval, Nidhi; Sheta, Soham; Vora, Lalitkumar K.; Elrashdy, Fatma; Redwan, Elrashdy M.; Uversky, Vladimir N.; Ertas, Yavuz Nuri (Frontiers in Immunology, 2023)
The newly emerged coronavirus (SARS-CoV-2) is virulent, contagious, and has rapidly gained many mutations, which makes it highly infectious and swiftly transmissible around the world. SARS-CoV-2 infects people of all ages and targets all body organs and their cellular compartments, starting from the respiratory system, where it shows many deleterious effects, to other tissues and organs. Systemic infection can lead to severe cases that require intensive intervention. Multiple approaches were elaborated, approved, and successfully used in the intervention of the SARS-CoV-2 infection. These approaches range from the utilization of single and/or mixed medications to specialized supportive devices. For critically ill COVID-19 patients with acute respiratory distress syndrome, both extracorporeal membrane oxygenation (ECMO) and hemadsorption are utilized in combination or individually to support and release the etiological factors responsible for the “cytokine storm” underlying this condition. The current report discusses hemadsorption devices that can be used as part of supportive treatment for the COVID-19-associated cytokine storm.